PENINGKATAN HASIL BELAJAR SISWA MELALUI METODE THINK PAIR PAIR SHARE DALAM GERAK MELINGKAR KELAS X MADRASAH ALIYAH NEGERI 2 PONTIANAK - Suminem, Suminem (Jurnal Pendidikan Matematika dan IPA, 2014)
In the first cycle implementing cooperative learning TPS the students’ mastery is as high as 18% of 33 students, the second cycle there is an increase to 48.48%. Because they have not reached minimal passing grade, the cycle is continued to the third cycle with the achievement grade 93.93% which is more than expectation. Therefore, the application of cooperative to study aims to improve students' mastery of learning outcomes in circular motion. The study was conducted on the class XF MAN 2 in even semester, using cooperative learning methods TPS with the helping of peer tutors. The researching forms an action research with 3 cycles. The results showed that polling method with the help of peer tutors can improve student learning outcomes in the thoroughness of the material optical instruments.Keywords: Cooperative polling, peer tutoring assistance.